ACUTE STRESS DISORDER VERSUS CHRONIC POSTTRAUMATIC STRESS DISORDER: INHIBITION OF FEAR AS A FUNCTION OF TIME SINCE TRAUMA. Issue 3 (20th August 2012) - Jovanovic, Tanja; Sakoman, Andrea Jambrošić; Kozarić‐Kovačić, Dragica; Meštrović, Ana Havelka; Duncan, Erica J.; Davis, Michael; Norrholm, Seth D.
<x xml:space="preserve">Abstract</x> Background Previous work has shown that inhibition of fear is impaired in posttraumatic stress disorder (PTSD) resulting from both civilian and combat trauma. The purpose of the present study was to investigate the inhibition of learned fear in traumatized individuals diagnosed with either acute stress disorder (ASD) or PTSD. This is the first study to use a conditioned inhibition paradigm with traumatized individuals within a month of trauma exposure. We hypothesized that impaired fear inhibition would be evident in PTSD, but not ASD. Method Using established translational, psychophysiological methods including fear‐potentiated startle, and skin conductance, we examined fear acquisition, stimulus discrimination, and the transfer of learned safety in a Croatian population with ASD or PTSD. This cross‐sectional study included three age‐matched groups: healthy nontrauma controls (n = 27), a group with chronic PTSD (10 or more years since trauma exposure, n = 24), and a group with ASD (30 days or less since trauma exposure, n = 27). Results The presence of trauma‐related psychopathology, whether acute or chronic, was associated with an impaired ability to transfer learned safety based on fear‐potentiated startle measures, while healthy control subjects showed significant fear inhibition in the presence of the safety cue compared to the danger cue, F(1, 26) = 12.64, P = .001. Conclusions These data expand our previously observed findings of PTSD‐associated fear inhibition deficits by demonstrating that trauma‐related impairments in safety learning are evident within 30 days of trauma exposure.